National Youth Service Corps Programme and the Quest for National Integration: Issues for Policy Consideration (Journal of Management and Social Sciences, 2018)
AbstractNigeria is a multi-ethnic, multi-lingual and multi religious nation and sadly all thesediversities have impacted adversely on her socio-political existence. The events of1966–1970 call to question the unity and continued existence of Nigeria as anethnically segmented nation. The Federal Military Government led by General YakubuGowon (rtd.) established the National Youth Service Corps (NYSC) programme as ameans of achieving national integration in the face of mutual suspicion and hostility.Adopting the descriptive analytical method, this paper identifies insecurity, generaldiscontent among parents, inadequate facilities, poor funding, and rejection of corpsmembers among others as challenges confronting the programme. The paper thereforerecommends improved funding of the programme, greater and sincere fight againstinsecurity, ethical re-orientation and religious tolerance as panacea to the challengesbeing faced by NYSC.